Theoretical Approach Including Friction for Determining Strain Limits in Punch Stretching of Anisotropic Sheet Metals - De Souza, L. H. B.; Menezes, M. A. [UNESP]; Moreira Filho, L. A.; Chinesta, F.; Chastel, Y.; ElMansori, M. (Amer Inst Physics, 2010)
A new analytical theory including friction was developed to assess strain limits in punch stretching of anisotropic sheet metals. This new approach takes into consideration the anisotropic behaviour of sheet materials and could explain the mechanical behaviour of a variety of anisotropic sheet materials. The theory explains the sheet metal failure so for the drawing as the stretching region of the forming limit curve, particularly for materials that present the strain-ratio dependence of limit strain epsilon(1), where d epsilon(1)/d rho is not always greater than zero. d epsilon(1)/d rho or d epsilon(1)/d epsilon(2) could be equal to or smaller than zero for a range of materials. Therefore, this new theory can explains such experimental observations, besides to assuming that membrane element relations near the pole, for the case of punch stretching are dependent of sheet metal properties as the process history and also suggests that the onset of local necking is controlled by shear. Thus, theoretical results obtained through this new approach are compared with experimental results available in the literature. It is demonstrated the effect of friction on a FLC curve for both regions, drawing and stretching.
Keywords: Sheet metal forming; punch stretching; strain limits; anisotropy; plastic instability and friction